(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of foliar application of water soluble fertilizers on growth and yield of chilli (Capsicum annuum L.) during 2015-16, 2016-17 and 2017-18 at Bharatpur, Rajasthan. The application of recommended dose of fertilizers-NPK @ 70:48:50) + water-soluble fertilizers (polyfeed NPK 19:19:19) @1% at 45 and 75 days after transplanting recorded higher yield of green chilli (93 q/ha) as compared to the control (84 q/ha). There was 10.71% increase in yield over the control .The technology gap in productivity (7 q/ha) was computed. The technology index value (7.53%) was recorded. The results indicated the gap existed in the potential yield and demonstration yield is due to soil fertility and weather conditions. By conducting on farm testing of proven technology of nutrient management, yield potential of chilli can be increased. This will substantially increase the income as well as the livelihood of farming community.